2019
DOI: 10.3390/jcm8070941
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Traditional Functionalities of Metastasis: The Parting of Ways with Real-Time Assays

Abstract: The experimental evaluation of metastasis overly focuses on the gain of migratory and invasive properties, while disregarding the contributions of cellular plasticity, extra-cellular matrix heterogeneity, niche interactions, and tissue architecture. Traditional cell-based assays often restrict the inclusion of these processes and warrant the implementation of approaches that provide an enhanced spatiotemporal resolution of the metastatic cascade. Time lapse imaging represents such an underutilized approach in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 166 publications
(219 reference statements)
1
0
0
Order By: Relevance
“…Whether MIR31HG knockdown also inhibits TGFβ-induced cell invasion warrants further investigation. The above study together with ours also implies that the effects of MIR31HG on cancer cell migration and invasion are uncoupled as reported earlier in other cancer cell types [ 49 , 50 ]. In addition, previous studies in non-small cell lung cancer and osteosarcoma cells also identified a promoting role of MIR31HG in the EMT [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 87%
“…Whether MIR31HG knockdown also inhibits TGFβ-induced cell invasion warrants further investigation. The above study together with ours also implies that the effects of MIR31HG on cancer cell migration and invasion are uncoupled as reported earlier in other cancer cell types [ 49 , 50 ]. In addition, previous studies in non-small cell lung cancer and osteosarcoma cells also identified a promoting role of MIR31HG in the EMT [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 87%